Cover Picture: Collective Synthesis of Schilancidilactones A, B and Schilancitrilactones A, B, C, 20‐epi‐Schilancitrilactone A (Chin. J. Chem. 3/2019). Issue 3 (13th February 2019) - Wang, Hengtao; Wang, Liang; Li, Yihang; Zhang, Xiunan; Tang, Pingping
Abstract : The cover picture shows Schilancidilactones A, B and Schilancitrilactones A, B, C all belong to schinortriterpenoid. Preliminary bioassay shows some of them possess fascinating bioactivities, such as antitumor, antihepatitis, and anti‐HIV‐1 activities. The total synthesis of Schilancidilactones A, B and Schilancitrilactones A, B, C has been accomplished from the common intermediates for the first time by Tang group. An intramolecular radical cyclization, late‐stage halogenation and AIBN‐mediated or Ni‐catalyzed intermolecular radical cross coupling reaction were employed as the key steps. More details are discussed in the article by Tang et al. on page 255–268. Abstract : The cover picture shows Schilancidilactones A, B and Schilancitrilactones A, B, C all belong to schinortriterpenoid. Preliminary bioassay shows some of them possess fascinating bioactivities, such as antitumor, antihepatitis, and anti‐HIV‐1 activities. The total synthesis of Schilancidilactones A, B and Schilancitrilactones A, B, C has been accomplished from the common intermediates for the first time by Tang group. An intramolecular radical cyclization, late‐stage halogenation and AIBN‐mediated or Ni‐catalyzed intermolecular radical cross coupling reaction were employed as the key steps. More details are discussed in the article by Tang et al. on page 255–268.